Phenyl quinoxalin-2-yl ether - Hassan, Nor Duha; Tajuddin, Hairul Anuar; Abdullah, Zanariah; Ng, Seik Weng (International Union of Crystallography, 2008)
The aromatic ring systems in the title compound, C(14)H(10)N(2)O, form a dihedral angle of 63.8 (1)°, resulting in an opening up of the ether-O atom angle to 118.2 (1)°.